Camphor, one of the essential oil constituent of Curcuma xanthorrhiza Rhizome from medicinal plant garden PT. Nyonya Meneer, Karangjati - ., Sudarsono (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
“Empon-empon” has been used as a raw material in most indonesian traditional medicine. Generally many of the indonesian traditional medicine consist of wild Curcuma species. Quality aspect of indonesian traditional medicine for its development in the future is needed. Consistency of the quality of the raw materials are becoming important to support product quality of traditional medicine. Wild raw materials are usually used as a indonesian traditional medicine, therefore the active substance or a charactistic metabolite in medicinal plant is one of the important thing to be found. Xanthorrhizol is one of the essential oil components of Curcuma xanthorrhiza Roxb. It has an affect on bile fluid secretion. Pure Xanthorrhizol as reference substance is still quite expensive. The aim of this research is to find out essential oil components that can be isolated. Steam destillation was used to isolate the essential oil, and the components of the essential oil was separated using column chromatography and thin layer chromatography. The identification of the isolated essential oil component was done by gas chromatography. Camphora is one of the Curcuma xanthorrhiza Roxb. essential oil that could be isolated in crystallin form.Key words: Camphora; essential oil; Curcuma xanthorrhiza Roxb